2013
DOI: 10.1038/nbt.2685
|View full text |Cite
|
Sign up to set email alerts
|

Identifying producers of antibacterial compounds by screening for antibiotic resistance

Abstract: Microbially derived natural products are major sources of antibiotics and other medicines, but discovering new antibiotic scaffolds and increasing the chemical diversity of existing ones are formidable challenges. We have designed a screen to exploit the self-protection mechanism of antibiotic producers to enrich microbial libraries for producers of selected antibiotic scaffolds. Using resistance as a discriminating criterion we increased the discovery rate of producers of both glycopeptide and ansamycin antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(158 citation statements)
references
References 33 publications
3
147
1
4
Order By: Relevance
“…However, since the antibiotic-producing strains must be resistant to the compounds they produce, Thaker et al (2013) applied antibiotic resistance in screening actinobacteria from soil, and they successfully isolated a strain producing a novel antibacterial glycopeptide. Many of the plant products applied in traditional medicine have antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the antibiotic-producing strains must be resistant to the compounds they produce, Thaker et al (2013) applied antibiotic resistance in screening actinobacteria from soil, and they successfully isolated a strain producing a novel antibacterial glycopeptide. Many of the plant products applied in traditional medicine have antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thaker et al recently reported the discovery of the novel glycopeptide pekiskomycin using growth in the presence of vancomycin as an initial screen to enrich for glycopeptide-producing strains derived from soil samples (44). A significant proportion of the vancomycin-resistant strains (89/100 strains) isolated in this way did not contain glycopeptide biosynthetic clusters, however, and it was necessary to include an additional PCR-based screen to identify those that did.…”
Section: Discussionmentioning
confidence: 99%
“…Following these findings, the synthetic derivative Cl-ARC was used for the stronger elicitation of BGCs encoding molecules at a low abundance in a panel of fifty Actinomycete strains. [65] This resulted in the identification of several CI-ARC-induced compounds including oxohygrolidin from Streptomyces ghanaensis, not previously known to produce this molecule. [66] Furthermore, based on bioactivity-guided assays, it was shown that while the extracts of the elicitor-treated S. ghanaensis failed to provide detectable inhibition, purified oxohydrolidin displayed activity against S. cerevisiae Y7092.…”
Section: Additional Approaches That Facilitate Streptomycetes Engineementioning
confidence: 99%